Pengaruh Influencer Marketing, Brand Image dan Cita Rasa Terhadap Keputusan Pembelian Pada Sate Bu Jumangin Kediri - Latifah, Faizatul; Pramutoko, Baju; Sholihin, Ustadus (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study discusses the influence of influencer marketing, brand image, and taste on purchasing decisions at Sate Bu Jumangin Kediri. The method used in this study is quantitative. The sample was obtained using the purposive sampling technique, with a total of 100 respondents. The data analysis techniques used include validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination (r2), t-test, and F-test. The results of the study indicate that influencer marketing significantly influences purchasing decisions with a significance level of 0.0004 < 0.05. Brand image has an effect but is not significant on purchasing decisions with a significance level of 0.203 > 0.05. Taste has an effect on purchasing decisions with a significance level of 0.001 < 0.05. All three variables show significant effects on purchasing decisions with a significance level of 0.001 < 0.05.